Synergism of Lumbricus rubellus and Pseudomonas putida Pf-20 in Inducing Resistance to Cucumber Mosaic Virus - WIWIEK SRI WAHYUNI; HARDIAN SUSILO ADDY; BUDI ARMAN; TRI CANDRA SETYOWATI (Bogor Agricultural University, Indonesia, 2006)
Both Lumbricus rubellus and Pseudomonas putida decompose soil organic matters. The population of P. putida Pf-20 increased if L. rubellus was introduced to the cucumber growth medium. The process of organic decomposition was much better if the medium was introduced with both L. rubellus and P. putida Pf-20, compared to the medium contained only either one of those organisms. The activity of L. rubellus may serve to provide nutrients for both the cucumber and P. putida. The role of P. putida to reduce disease severity was increased if L. rubellus was introduced to the growth medium. The synergism of these two organisms, reduced either the level of disease severity to CMV-48 and C/N ratio of medium, but increased the content of available phosphor and potassium. Key words: Lumbricus rubellus, Pseudomonas putida Pf-20, disease severity of CMV